Schoenus inconspicuus (Cyperaceae, tribe Schoeneae): a new species from Southern Africa - Elliott, Tammy Lynn; Euston-Brown, Doug I. W.; Muasya, A. Muthama (Phytotaxa, 2020)
Schoenus is a predominately austral genus of sedges in which the Southern African taxa have recently received detailed taxonomic attention, starting with a transfer of 24 species into Schoenus from Tetraria and Epischoenus in 2017. The taxonomy of the Southern African Schoenus species is currently being revised, which has brought insight into the existence of several species new to science. Here, we build on this recent taxonomic work by describing one new species that has been previously overlooked (Schoenus inconspicuus), while including a distribution map, an assessment of conservation status and an updated identification key.